2022
DOI: 10.5853/jos.2022.00906
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Acute Stroke Patients with Moderate to Severe Pre-Stroke Disability

Abstract: Background and Purpose Studies on mechanical thrombectomy (MT) in acute ischemic stroke (AIS) patients with preexisting disability are limited. We aimed to compare the outcomes of MT versus best medical treatment (BMT) in these patients. Methods In the nationwide Austrian registry and Swiss monocentric registry, we identified 462 AIS patients with pre-stroke disability (modified Rankin Scale [mRS] score ≥3) and acute large vessel occlusion. The primary outcome was returning to pre-stroke mRS or better at 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In another study, Sykora et al studied effects of MT vs. BMM in LVO patients with pre-stroke mRS ≥3 using propensity score matching. 168 patients in each group were identified and it showed MT was associated with higher odds of returning to baseline mRS at 3 months, early neurological improvement, and lower risk of 3-month mortality without increased risk of sICH [33]. A Japanese study of 339 LVO mRS 2-4 patients showed again MT was associated with higher odds of return to baseline function at 3 months than BMM (28.0 vs. 10.9%), and sICH rates were similar between the groups.…”
Section: Pre-stroke Modified Rankin Scale (Mrs)mentioning
confidence: 99%
“…In another study, Sykora et al studied effects of MT vs. BMM in LVO patients with pre-stroke mRS ≥3 using propensity score matching. 168 patients in each group were identified and it showed MT was associated with higher odds of returning to baseline mRS at 3 months, early neurological improvement, and lower risk of 3-month mortality without increased risk of sICH [33]. A Japanese study of 339 LVO mRS 2-4 patients showed again MT was associated with higher odds of return to baseline function at 3 months than BMM (28.0 vs. 10.9%), and sICH rates were similar between the groups.…”
Section: Pre-stroke Modified Rankin Scale (Mrs)mentioning
confidence: 99%